Dietary Insights in Gout Management: A Descriptive Exploration of Eating Patterns - Dwi Webrianti; Yuliarti Yuliarti (Proceedings Series on Health & Medical Sciences, 2024)
Background: Indonesia ranks fourth in the world for the highest gout arthritis cases, accounting for 35% of the population. Gout arthritis is a degenerative disease caused by an excessive accumulation of uric acid in the blood. Uric acid is primarily obtained from food; thus, improper dietary behavior can increase uric acid levels in the blood, triggering sudden attacks. Objective: To describe the dietary behavior patterns among patients with gout in Mangunharjo Village, Adimulyo Sub-district, Kebumen Regency. Method: This study utilized a descriptive approach with a case studies qualitative method, collecting data through interviews, observations, and document analysis. The study involved 17 participants (7 primary and 10 triangulation informants) selected through purposive sampling. Results: The majority of informants were employed as farmers. Knowledge regarding the causes of gout remained low, and in terms of dietary behavior, most participants needed more discipline in adhering to a purine-restricted diet. Environmental factors, economic circumstances, and habits related to purine consumption influenced this behavior. Conclusion: Positive dietary behavior is significantly influenced by knowledge levels. Such behavior also requires support from environmental factors, conditions, family, and the need to alter dietary habits.